The Dynamics of English/Englishes in the Globalised World: A Sociolinguistic Outlook - Aby John (Recent Research Advances in Arts and Social Studies Vol. 7, 2024)
English is also known as the “world language” or “global language” due to its wide usage. It is used by millions of people in their day-to-day life for writing, speaking, and for various other means of communication. Many countries have officially recognized English as one of their official languages. It is one of the subjects in the curriculum of major universities. This paper sheds light on the significance of the English language from the perspective of globalization. It delves into the depth of the relevance of English in the process of globalization. One must also understand that English paves way to more educational resources, employment opportunities, and helps to develop many other valuable life skills. Moreover, novel varieties of English or World Englishes gain power over the native/pure form of British/American English.